Studies in Gusii kinship - Mayer, Iona (Rhodes University, Faculty of Humanities, Department of Anthropology, 1966)
This thesis has two aims. In Part I the aim is to present some unpublished field material on Gusii kinship, particularly on domestic relations between the generations and the sexes. In Part II the aim is to clarify a theoretical model of 'relation by kinship', and of ' kinship categories" and 'classificntion', based on an examination of the ways in which Gusii use kinship terms. Intro., p. 1.
Keywords: Gusii (African people) -- Kinship